Factors Influencing the Design of Parabolic Trough Collector: A Review - Navish Kumar (International Journal of Energy and Thermal Applications, 2024)
Due to limited resource availability and high conventional energy usage, research into renewable energy has increased during the past few years. Utilizing collecting systems, significant renewable energy can be produced from the available solar radiation. The majority of solar energy harvesting systems use parabolic trough concentrating collectors. The performance of parabolic trough collectors as a whole is examined in this paper. The operating characteristics, such as the type of receiver and collector material, the medium for heat transfer, the type of application, and varied environmental conditions, all affect the performance.
Keywords: Radiation; efficiency; energy; parabolic trough collector; thermal analysis